Growth rate variation of the stalked barnacle Pollicipes pollicipes (Crustacea: Cirripedia) using calcein as a chemical marker. - Jacinto, David (2016)
This study describes the use of calcein as a chemical tagging methodology to estimate growth rate variation of the stalked barnacle Pollicipes pollicipes, an ecologically important intertidal species and economic resource, in SW Portugal. Calcein tagging had a high success rate (94%) in marking both juvenile and adult barnacles for a period of 2.5 months, pro- viding a valuable method for obtaining reliable data in growth studies of P. pollicipes. Growth rate decreased with barnacle size and was highly variable amongst individuals, particularly in smaller barnacles. No effect of shore level on barnacle growth was detected. Growth rates were higher in smaller juvenile barnacles, peaking at a 1.1-mm monthly increment in rostro-carinal length (RC) for individuals with RC=5 mm, and decreased with barnacle size (monthly growth rates of 0.5 mm for adult barnacles with RC~12.5 mm). Growth rates observed in adults with commercial interest (RC␣18 mm) was <0.25 mm per month. The advantages of tagging P. pollicipes with calcein were the possibility of mass marking individual barna- cles of different size cohorts within a short period (less than 1 day of manipulation); and reduced time of fieldwork, which is very important because this species inhabits very exposed rocky shores.